Changes in gastric environment with test meals affect the performance of 14C-urea breath test - PATHAK, CHANDER M; BHASIN, DEEPAK K; NADA, RITAMBARA; BHATTACHARYA, ANISH; KHANDUJA, KRISHAN L (Journal of gastroenterology and hepatology, 2005)
Background:  14C‐urea breath test (UBT) is considered to be an accurate diagnostic test for the detection of active Helicobacter pylori infection. Various test meals are used in 14C‐UBT to slow down gastric emptying, and to enhance the gastric distribution, in order to increase the time and area of contact between microorganisms and the tracer substrate. The aim of the present paper was to evaluate the effect of gastric environment on the performance of 14C‐UBT using an alkaline and an acidic liquid test meal having gastric emptying retardant effect. Methods:  The comparison of 14C‐UBT was done with liquid test meals (200 mL water) comprising (i) plain drinking water (PDW); (ii) 1.3 g or 3.0 g citric acid (CA); and (iii) 3.0 g trisodium citrate (TSC). Eighteen patients (37 ± 12 years, range 18–57 years) with complaints of dyspepsia participated in the study. The status of H. pylori was confirmed by histology and rapid urease test. A total of 93 kBq of 14C‐urea (0.5 mL) in a gelatin capsule was orally administered along with liquid test meals to the overnight fasting subjects. Breath samples were collected and radioactivity measured. Results were expressed as 14CO2/mmol exhaled CO2 as percentage of administered radioactive urea. Results:  Higher acidic gastric environment (pH approx. 2.0) with CA was found to increase the exhaled 14CO2 level in a dose‐dependent manner as compared to PDW and TSC meal (P < 0.05) at all time points. With TSC test meal, the expired 14CO2 level decreased in the lower acidic gastric environment (pH approx. 5.3). The peaks of exhaled 14CO2 with TSC test meal were observed at the same time points as that with PDW and CA test meals. The 14C‐UBT with TSC was found to be positive in 77% of patients (10/13). Conclusion:  Better interaction between the microbial urease and 14C‐urea, caused by a test meal that retards gastric emptying and that changes gastric pH, plays an important role in hydrolysis of the administered 14C‐urea by H. pylori urease. © 2005 Blackwell Publishing Asia Pty Ltd